Skip-beat! 17 - Nakamura, Yoshiki (Shojo beat manga., 2009)
"Kyoko Mogami followed her true love Sho to Tokyo to support him while he made it big as an idol. But he's casting her out now that he's famous! Kyoko won't suffer in silence--she's going to get her sweet revenge by beating Sho in show biz! Dark Moon is getting excellent ratings, and Kyoko is getting tons of offers for more acting jobs! But all the offers are for twisted, damaged characters like Mio. Kyoko doesn't want to get stuck as a character actor, and she certainly doesn't want to play freaks for the rest of her career. But if she refuses all these jobs, will she even have a career left?!"--p. [4] of cover.